2022
DOI: 10.1111/1750-3841.16207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of structural and antioxidant activity of polysaccharide extracted from truffles

Abstract: As the main component of truffles, polysaccharides have a variety of biological activities such as anti-oxidation, anti-tumor, and hypoglycemic activity, and these activities are closely related to its structure. In this study, Tuber Aestivum crude polysaccharide (TACP) and Tuber Melanosporum crude polysaccharide (TMCP) were obtained from Tuber Aestivum and Tuber Melanosporum by using microwave-assisted hot water, and then the Sephadex G-200 column was utilized to further separate and purify Tuber Aestivum pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…At 1077.78018 cm −1 was the β-pyranose ring in the glucose residue. The results indicated that FVP might be β-pyran polysaccharides (Guan et al, 2022;Zhang et al, 2018) (Figure S1d).…”
Section: Discussionmentioning
confidence: 98%
“…At 1077.78018 cm −1 was the β-pyranose ring in the glucose residue. The results indicated that FVP might be β-pyran polysaccharides (Guan et al, 2022;Zhang et al, 2018) (Figure S1d).…”
Section: Discussionmentioning
confidence: 98%
“…The results suggested that OFPPs exhibited protective effect on Huh-7 cells against H 2 O 2 -induced oxidative stress and increased the viability of the cells. Polysaccharide extracted from truffles has also been reported to enhance the viability of the H 2 O 2 -induced IPC-J2 cells and protect the cells from oxidative stress [54] . The anti-oxidative stress activity of OFPPs can be further explored by determining the level of intracellular oxidative stress.…”
Section: Nmr Analysis Of Ofpp-3mentioning
confidence: 99%
“…Polysaccharides with low MW have the potential to penetrate into immune cells and generate an immune response [20]. However, the antioxidant property of a polysaccharide is inversely associated with its MW, i.e., polysaccharides with lower molecular exhibit greater antioxidant activity, whereas high-MW polysaccharides are thought to have potent immunomodulatory and anti-tumor activities [20][21][22].…”
Section: Introductionmentioning
confidence: 99%